Epidemiological Data from Patients Who Underwent Colonoscopy from High-Susceptibility Vacancies - Ana Claudia Martins; Vera Lúcia Miranda; Milton Brandão Monteiro Junior; Mayra dos Santos Silva (Journal of Coloproctology)
Objective The objective of this study was to analyze the epidemiological profile of patients to propose measures that facilitate regulation and access to diagnostic imaging exams.